Nitrogen Starvation and the Regulation of Glutamine Synthetase in Agmenellum quadruplicatum - Paone, Domenic A. M. (1981)
The level of glutamine synthetase activity in Agmenellum quadruplicatum strain PR-6 was dependent on the nitrogen source used for growth and on the nutritional status of the cells. During exponential growth, glutamine synthetase activity was low in cells grown on ammonia, urea, or nitrate. During the transition from nitrogen replete to nitrogen starved growth, glutamine synthetase activity began to rise. With ammonia as a nitrogen source, glutamine synthetase activity as determined in whole cells increased from 1 nanomole per minute per milliliter during exponential growth to 22 nanomoles per minute per milliliter during severe nitrogen starvation. In cells grown on nitrate the increase was from 5 to 39 nanomoles per minute per milliliter, and in cells grown on urea the increase was from 4 to 31 nanomoles per minute per milliliter. The rise in glutamine synthetase activity corresponded with the rapid decline in the nitrogen and c-phycocyanin content of the cells. Prior to nitrogen starvation, the nitrogen content of the cells was 140, 90, and 83 micrograms nitrogen per milligram dry weight for ammonia, urea, and nitrate grown cells, respectively. During nitrogen starvation where glutamine synthetase activity was highest, the nitrogen content of cells had declined to 35 to 40 micrograms nitrogen per milligram dry weight of cells. At the same time, the c-phycocyanin content of cells dropped by 95%.